Gallstone Disease and the Risk of Cardiovascular Disease: A Systematic Review and Meta-Analysis of Observational Studies. (March 2017) - Upala, S.; Sanguankeo, A.; Jaruvongvanich, V.
Objectives: Gallstone disease shares certain risk factors with cardiovascular disease, particularly metabolic risk factors. Patients with gallstone disease may be at increased risk of cardiovascular disease. Several recent studies exploring the effect of gallstone disease on cardiovascular disease outcomes demonstrated inconsistent results. Design: We conducted a systematic review and meta-analysis of cohort, case–control, and cross-sectional studies that compared the risk of developing cardiovascular disease events in patients with gallstone disease versus non-gallstone disease controls. Data from each study were combined using the random-effects, generic inverse variance method of DerSimonian and Laird to calculate the pooled hazard ratio, odd ratio, and 95% confidence interval. Results: Data were extracted from six studies involving 176, 734 cases and 803, 714 controls. The pooled hazard ratio of cardiovascular events in patients with gallstone disease was 1.28 (95% confidence interval: 1.23–1.33, I 2 = 42%). The pooled odd ratio of cardiovascular events in patients with gallstone disease was 1.82 (95% confidence interval: 1.47–2.24, I 2 = 68%). Conclusions: Our study demonstrated a statistically significant increase in the risk of cardiovascular disease among patients with gallstone disease.